1994
DOI: 10.1002/kin.550260606
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated α‐ketocarbenes: Formation and isomerization reactions. RRKM calculations with semi‐empirical parameters (AM1, MNDOC)

Abstract: The dynamical aspects of some a-diazoketones (DZ) photolysis are investigated within the framework of statistical theories (RRKM formulation). On the whole, the results agree satisfactorily with the gasphase experimental observations (quantum yields). In particular, the reactions DZ + hv -, a-ketocarbene (KC) + Nz, appear to be mainly governed by statistical behavior. The two channel isomerizations KC -, ketene (KE), i.e, the Wolff Rearrangement, and KC -a, P-unsaturated ketone (ON) are also considered.It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…H, and Me, respectively, in ethylmethylcarbene. [81] Semiempirical (AM1) methods were employed to compare 24 with 38, [82] and to analyze substituent effects on the rearrangement of 25. [83] A comprehensive theoretical investigation of migratory aptitudes has yet to appear.…”
Section: Migratory Aptitudesmentioning
confidence: 99%
“…H, and Me, respectively, in ethylmethylcarbene. [81] Semiempirical (AM1) methods were employed to compare 24 with 38, [82] and to analyze substituent effects on the rearrangement of 25. [83] A comprehensive theoretical investigation of migratory aptitudes has yet to appear.…”
Section: Migratory Aptitudesmentioning
confidence: 99%
“…In our case the singlet±triplet gap is predicted to be about 2 kcal/mol at UB3LYP/6-31G** level, and so both species can exist in rapid equilibrium [13]. Nevertheless, it has been reported that the shifts on the triplet ground-state PES have larger energy barriers than that on the ®rst singlet-state PES [30,32]. Therefore, in this paper we shall deal with the shifts on the ®rst excited singlet-state PES, i.e.…”
Section: Regular Articlementioning
confidence: 76%